A case for change in teacher preparation : developing community-based residency programs - Gorlewski, Julie A. (New York, NY : Routledge, 2022)
"This book describes a reconceptualized teacher preparation program based on a teacher residency model. Through a combination of rich description, and qualitative and quantitative program data, the authors make the case that university programs focused on the communities they serve can ensure more effective, learner-ready teachers who remain in the profession longer. By providing a detailed blueprint for program development, the contents of this book will be of value and interest to educational leaders, policymakers, and researchers"--
Keywords: Teachers -- Training of -- United States; Community and school -- United States; Educational change -- United States; Teachers colleges -- Curricula -- United States; EDUCATION / General